PLL Instability of Wind Turbines During Severe Faults - Arasteh, Amir; Cutululis, Nicolaos A. (IEEE access, 2022)
Stringent grid codes require wind turbines (WTs) to remain connected even during severe faults. This can result in PLL instability and Loss of Synchronisation (LoS), which is the main subject of this paper. For a better understanding, the phenomenon is analysed in the dq equivalence. The presented analysis enlightens the root cause of the associated instability and clarifies the key role of PLL in that. Based on this analysis, a hybrid solution combining an Adaptive-PLL with impedance estimation is proposed. In this regard, the PLL-gains during the fault are selected in accordance with accuracy of the impedance estimation: the higher the accuracy of the estimation, the lesser the required changes in the gains of PLL. The work also proposes a logical circuit for a more reliable detection of LoS, allowing the controller to only act when necessary. Simulation results and discussions support the proposals.